Respuesta :

p   …   q   …   ¬q   …   p ∨ ¬q   …   (p ∨ ¬q) ⇒ q

T   …   T   …    F   …        T        …          T

T   …   F   …    T   …        T        …          F

F   …   T   …    F   …        F        …          T

F   …   F   …    T   …        T        …          F

Start with the first two columns, taking every possible pair of True/False for p and q.

¬q is just the negation of q, so True becomes False and False becomes True.

pq is the logical disjunction, or logical "or". It's True if either p or q is True, and False otherwise. So p ∨ ¬q is True only if either p or ¬q is True.

pq is the logical implication. It's True only when both p and q are True, or when p is False. So (p ∨ ¬q) ⇒ q is True when both p ∨ ¬q and q are True, or when p ∨ ¬q is False.